STATUS OF USE OF RENEWABLE ENERGY SOURCES IN KHORAZM REGION AND SIGNIFICANCE OF INNOVATIONS IN ITS DEVELOPMENT (Marketing Journal, 2025)
This study focuses on examining the current state of renewable energy sources (RES) utilization in the Khorezm region and evaluating the role of innovations in their development. The region has identified significant potential in solar (1900 million kWh/ye ar), wind (114.6 million kWh/year), and hydropower (45.2 million kWh/year), yet these capacities are currently underutilized. The study analyzes existing RES projects in the region, evaluates innovative technologies (smart grid, energy storage 568 systems, agrivoltaics), identifies key development barriers, and proposes strategies for overcoming them. The economic efficiency of RES projects and their development prospects up to 2030 are assessed. Recommendations are provided on innovative directions such as hydrogen energy, agrivoltaics, and hybrid systems.
Keywords: renewable energy sources; innovative technologies; solar energy; agrivoltaics; smart grid; hydrogen energy